The loss of photosynthetic pathways in the plastid and nuclear genomes of the non-photosynthetic mycoheterotrophic eudicot Monotropa hypopitys. (November 2016) - Ravin, Nikolai; Gruzdev, Eugeny; Beletsky, Alexey; Mazur, Alexander; Prokhortchouk, Egor; Filyushin, Mikhail; Kochieva, Elena; Kadnikov, Vitaly; Mardanov, Andrey; Skryabin, Konstantin
Abstract Background Chloroplasts of most plants are responsible for photosynthesis and contain a conserved set of about 110 genes that encode components of housekeeping gene expression machinery and photosynthesis-related functions. Heterotrophic plants obtaining nutrients from other organisms and their plastid genomes represent model systems in which to study the effects of relaxed selective pressure on photosynthetic function. The most evident is a reduction in the size and gene content of the plastome, which correlates with the loss of genes encoding photosynthetic machinery which become unnecessary. Transition to a non-photosynthetic lifestyle is expected also to relax the selective pressure on photosynthetic machinery in the nuclear genome, however, the corresponding changes are less known. Results Here we report the complete sequence of the plastid genome ofMonotropa hypopitys, an achlorophyllous obligately mycoheterotrophic plant belonging to the familyEricaceae . The plastome ofM. hypopitys is greatly reduced in size (35, 336 bp) and lacks the typical quadripartite structure with two single-copy regions and an inverted repeat. Only 45 genes remained presumably intact– those encoding ribosomal proteins, ribosomal and transfer RNA and housekeeping genesinfA, matK, accD andclpP . TheclpP andaccD genes probably remain functional, although their sequences are highly diverged. The sets of genes for ribosomal protein and transfer RNA are incomplete relative to chloroplasts of a photosynthetic plant. Comparison of the plastid genomes of two subspecies-level isolates ofM. hypopitys revealed major structural rearrangements associated with repeat-driven recombination and the presence of isolate-specific tRNA genes. Analysis of theM. hypopitys transcriptome by RNA-Seq showed the absence of expression of nuclear-encoded components of photosystem I and II reaction center proteins, components of cytochromeb6f complex, ATP synthase, ribulose bisphosphate carboxylase components, as well as chlorophyll from protoporphyrin IX biosynthesis pathway. Conclusions With the complete loss of genes related to photosynthesis, NADH dehydrogenase, plastid-encoded RNA polymerase and ATP synthase, theM. hypopitys plastid genome is among the most functionally reduced ones characteristic of obligate non-photosynthetic parasitic species. Analysis of theM. hypopitys transcriptome revealed coordinated evolution of the nuclear and plastome genomes and the loss of photosynthesis-related functions in both genomes.